The midnight bell [large type] - Higgins, Jack, 1929- (Thorndike Press, A part of Gale, Cengage Learning, 2017)
"In Washington, D.C., on a night full of rain, a woman is struck down and killed by a hit-and-run driver. But she is not just any woman--she is the assistant to the head of the secret White House department known only as the Basement. And she had secrets of her own. In the Virgin Islands, former president Jake Cazalet receives a warning. He is recuperating on a diving trip after successfully helping Sean Dillon and the rest of the "Prime Minister's private army" defeat an Al Qaeda operation in London. But though AQ may be weakened and facing competition from other terrorist upstarts, it is far from dead--and it intends to prove it. Soon the ripples from these two events will spread and overlap, not only in Washington but around the world. Everyone involved will find themselves in the most desperate battle of their lives--and the midnight bell will toll"--